Genetic Resources of Cereal Crops for Aphid Resistance - Radchenko, Evgeny E.; Abdullaev, Renat A.; Anisimova, Irina N. (Plants (Basel), 2022)
The genetic resources of cereal crops in terms of resistance to aphids are reviewed. Phytosanitary destabilization led to a significant increase in the harmfulness of this group of insects. The breeding of resistant plant genotypes is a radical, the cheapest, and environmentally safe way of pest control. The genetic homogeneity of crops hastens the adaptive microevolution of harmful organisms. Both major and minor aphid resistance genes of cereal plants interact with insects differentially. Therefore, rational breeding envisages the expansion of the genetic diversity of cultivated varieties. The possibilities of replenishing the stock of effective resistance genes by studying the collection of cultivated cereals, introgression, and creating mutant forms are considered. The interaction of insects with plants is subject to the gene-for-gene relationship. Plant resistance genes are characterized by close linkage and multiple allelism. The realizing plant genotype depends on the phytophage biotype. Information about the mechanisms of constitutional and induced plant resistance is discussed. Resistance genes differ in terms of stability of expression. The duration of the period when varieties remain resistant is not related either to its phenotypic manifestation or to the number of resistance genes. One explanation for the phenomenon of durable resistance is the association of the virulence mutation with pest viability.